Competitive ability of breeds of leaf rust from of crystalline wheats - Huerta Espino, Julio; Singh, Ravi; Villaseñor Mir, Héctor Eduardo; Rodríguez García, María Florencia; Solís Moya, Ernesto; Espitia Rangel, Eduardo (Revista Mexicana de Ciencias Agrícolas, 2020)
In the process of genetic improvement of wheat, the evaluation of genotypes for resistance to rusts is essential; often breeders must mix different races; however, it is essential to know the competitive hability of the rust, and the wheat genotype used for increase. The aim of the study was to measure the competitive ability of four-leaf rust races caused by Puccinia triticina E. attacking durum wheat (Triticum durum L.). The study was conducted in a greenhouse during the year 2015. Leaf rust races BBG/BN, BCG/BN, BBG/BP and CBG/BP, were proportionally mixed and multiplied for three successive generations in the susceptible genotypes (Atil C2001 and Morocco); resistant genotypes: (Samayoa C2004 and Thatcher-Lr16 (RL6005]) in addition to them Júpare C2001 resistant to BBG/BN and BCG/BN, but susceptible to BBG/BP and CBG/BP. After urediniospore multiplication, 100 single pustule isolates obtained were increased in the cultivar Morocco before proceeded to the race identification. The most frequently identified race was CBG/BP with 46%, followed by BBG/BP with 34% and BBG/BN with 18%. BCG/BN was the less frequent with 2%. Only among urediniospores composite mass (CM) obtained from RL6005 and Morocco allowed the identification of the four races; in Atil C2001, Júpare C2001 Samayoa C2004 allowed the identification of three. The race identified more frequently in Atil C2001, RL6005 and Samayoa C2004 was BBG/BP, while in Morocco and Júpare C2001, CBG/BP. It is concluded that CBG/BP is more competitive than BBG/BP, BBG/BN and BCG/BN and it is recommended to be used in the mixture.